Rearrangement of indigenous spaces - Sablin, Ivan (Interventions, 2014)
This essay addresses the period when Chukotka, a distant region in the Northeast of the USSR, was incorporated into the state. This was done primarily by rearrangement of indigenous people's spaces. The establishment of new centres of domination and collectivization was accompanied by a major shift in the official attitude towards the indigenous population of the region, and by the depreciation of their role in the exploitation of natural resources. The reconfiguration of spaces was carried out by means of repressive measures and produced major grievances and resistance among the indigenous population. The Second World War further aggravated the situation. The incorporation of Chukotka into the Soviet state resulted in the disruption of indigenous economies and a major decline in population. The essay relies on the methodology of colonial and postcolonial studies, employing and developing the notion of space reorganization used by Gray, Crush, Neumann and other authors, and Bhabha's concept of ‘third space’.
Published online: 23 Oct 2013
Gesehen am 27.05.2019